Sistem Pendukung Keputusan Kelayakan Pengajuan Kredit Tunai Berdasarkan Agunan dengan Metode Electre - Najirah Umar; Suwatri Jura; Jefry Samuel (Prosiding SISFOTEK, 2023)
This study aims to implement a decision support system on the feasibility of requesting a cash loan against collateral using the Electre method. The research methodology uses the Waterfall system development model, Research in the context focuses on efforts or actions aimed at improving the quality and performance of an organization. Data collection techniques in system design include documentation, observation, compiling questionnaires, and conducting interviews. The system processes data from the results of surveys of interested parties conducted by experts. The assessment results are processed electrically to obtain solvency results. Research results show that the decision support system on the feasibility of applying for a cash loan based on collateral using the Electre method can help companies determine the provision of credit to customers . Using this method effectively increases accuracy, efficiency and risk management in the credit decision-making process. This system brings huge benefits to financial services, customers and the entire banking industry.